Loss-of-function and gain-of-function mutations in PPP3CA cause two distinct disorders. (8th February 2018) - Mizuguchi, Takeshi; Nakashima, Mitsuko; Kato, Mitsuhiro; Okamoto, Nobuhiko; Kurahashi, Hirokazu; Ekhilevitch, Nina; Shiina, Masaaki; Nishimura, Gen; Shibata, Takashi; Matsuo, Muneaki; Ikeda, Tae; Ogata, Kazuhiro; et al.
Abstract: Calcineurin is a calcium (Ca 2+ )/calmodulin-regulated protein phosphatase that mediates Ca 2+ -dependent signal transduction. Here, we report six heterozygous mutations in a gene encoding the alpha isoform of the calcineurin catalytic subunit ( PPP3CA ). Notably, mutations were observed in different functional domains: in addition to three catalytic domain mutations, two missense mutations were found in the auto-inhibitory (AI) domain. One additional frameshift insertion that caused premature termination was also identified. Detailed clinical evaluation of the six individuals revealed clinically unexpected consequences of the PPP3CA mutations. First, the catalytic domain mutations and frameshift mutation were consistently found in patients with nonsyndromic early onset epileptic encephalopathy. In contrast, the AI domain mutations were associated with multiple congenital abnormalities including craniofacial dysmorphism, arthrogryposis and short stature. In addition, one individual showed severe skeletal developmental defects, namely, severe craniosynostosis and gracile bones (severe bone slenderness and perinatal fractures). Using a yeast model system, we showed that the catalytic and AI domain mutations visibly result in decreased and increased calcineurin signaling, respectively. These findings indicate that different functional effects of PPP3CA mutations are associated with two distinct disorders and suggest that functional approaches using a simple cellular system provide a tool for resolving complex genotype–phenotype correlations.